The Role of Self-Efficacy on Job Readiness and Career Choice Among People with Intellectual Disability in Singapore - Li, Jen-Yi; Goh, Li Li (Journal of the American Academy of Special Education Professionals, 2011)
The study examined the role of general and social self-efficacy on job readiness and career choices among youths with intellectual disabilities (ID) in Singapore. Forty-seven students were recruited, with an IQ ranging from 50 to 70. Results showed that general self-efficacy was moderately related to social self-efficacy, but highly related to job readiness. Three self-report instruments were administered, including: the General Self-Efficacy Scale-ID version, the Glasgow Social Self-Efficacy Scale, and the Job Readiness Scale-ID version. Students were also asked to indicate their career choices and provided their demographic characteristics through a semi-structured questionnaire. Research findings provided both special educators and vocational rehabilitation professional with information on the importance of self-efficacy and suggested for interventions aimed at developing students’ self-efficacy to improve their job readiness.